The key factors influencing the purchase intention towards LCCs: the case of Chinese college students - Zheng, Xuan (2019)
The aviation market of China has become the second largest one in the world and its rapid growth is predicted to continue in next decades. However, few academic attentions have been given to the underdevelopment of LCCs in China and the behaviors of Chinese air passengers, especially college students as the second large customer source. As a result, the first purpose of this study is to identify the factors that have influence on Chinese college students’ behavioral intention to use LCCs; the second purpose is to develop a good model particularly to study China’s LCCs market; the third purpose is to give strategic recommendations to foreign LCCs firms which value the market potential of China and plan to extend their business in China. To achieve these purposes, an extended TPB model is introduced to this study and SEM is used to analyze the data. The data is collected by survey and interviews in two airports, with 115 questionnaires and 8 face-to-face interviews meeting the minimum sample requirement. The result indicates attitude, subjective norms, price, frequency, Mianzi and PBC have positive direct influence on the Chinese college students’ behavioral intention towards LCCs, while service quality can only have indirect influence on behavioral intention via attitude. Based on the findings, recommendations are provided to LCCs firms. Firstly, college students deserve marketing attention because they would become good customer source in the future. Secondly, marketing strategies of LCCs firms should consider the factors and their influence identified by this study to adapt to the specific demands of China’s aviation market.